Trade-offs between horizontal and vertical velocities during triple jumping and the effect on phase distances - Allen, S. J.; King, M. A.; Yeadon, M. R. (Journal of Biomechanics, 2013)
The triple jump is an athletic event involving three ground contact phases during which athletes must trade off the maintenance of horizontal velocity against the generation of vertical velocity. Previous studies have indicated that individual athletes have a linear relationship between the loss in horizontal velocity and the gain in vertical velocity during each phase. This study used computer simulation to investigate the effects of constraining the takeoff velocities in the hop phase on the velocity trade-offs in this and subsequent phases. Kinematic data were obtained from an entire triple jump using a Vicon automatic motion capture system, and strength and anthropometric data were collected from the triple jumper. A planar 13-segment torque-driven subject-specific computer simulation model was used to maximise the distance of each phase by varying torque generator activation timings using a genetic algorithm. Vertical takeoff velocities in the hop phase were constrained to be 100%, ±10%, ±20%, and ±30% of the performance velocity, and subsequent phases were optimised with initial conditions calculated from the takeoff of the previous phase and with no constraints on takeoff velocity. The results showed that the loss in horizontal velocity during each contact phase was strongly related to the vertical takeoff velocity (R2=0.83) in that phase rather than the overall gain in vertical velocity as found in previous studies. Maximum overall distances were achieved with step phases which were 30% of the total distance of the triple jump confirming the results of experimental studies on elite triple jumpers.